Conservation Concerns of Small-Scale Fisheries: By-Catch Impacts of a Shrimp and Finfish Fishery in a Sri Lankan Lagoon - Jones, Benjamin L.; Unsworth, Richard K. F.; Udagedara, Susantha; Cullen-Unsworth, Leanne C. (Frontiers in Marine Science, 2018)
By-catch is considered a significant problem in large-scale fisheries yet in small-scale fisheries (SSF), employing >99% of the world's fishers, there is limited quantitative understanding of by-catch, and catches in general. We provide an assessment of by-catch from fishing gears (fyke, trawl, set trammel & drift trammel nets) commonly used in small-scale fisheries across the globe, using a representative Sri Lankan case study and placing this in the context of local resource use patterns. We reveal evidence of how SSF generate significant finfish by-catch with potentially significant ecological impacts. Fishers targeting shrimp (fyke, trawl and drift trammel nets) caught more non-target species than global averages (44%, 44% and 67% by weight respectively). Fishers targeting finfish (set trammel nets) caught fewer non-target species. We found that by-catch depends more on target species and gear type, supporting suggestions that SSF are not “inherently more sustainable” than their large-scale counterparts and a collective effort is required for an improved understanding of the impacts of SSF. This study highlights an additional issue of valuable food fish discards, raising questions about fisheries exploitation in the context of food security in areas where poverty and food insecurity are prevalent.